Going green: Impact of green supply chain management practices on sustainability performance - Ahmad, Azhar; Ikram, Amir; Rehan, Muhammad Farooq; Ahmad, Ayyaz (Frontiers in Psychology, 2022)
The rising environmental challenges are capturing the attention of stakeholders of corporations due to increasing competition. The sustainable performance of firms does not merely gauge the economic performance but also their sustainable development. Since the environmental supply chain management of firms has an important part in maneuvering their sustainable performance, the present study focuses on assessing the impact of Green Supply Chain Management practices on the sustainable performance of textile, automobile and tobacco industries. The data collected from 332 organizations, analyzed through SPSS and AMOS. The results reveal that the impact of green manufacturing, green purchases, eco-design, and green information system are significant and positive on the sustainable performance of the organizations, whereas the impact of cooperation with customers is insignificant. Similarly, the moderation of institutional pressures between green manufacturing, green purchases, eco-design, and sustainability performance is insignificant, whereas it significantly moderates between cooperation with customers, green information system and sustainable performance. The study is significant and novel for considering five different factors of green supply chain management (GSCM): green manufacturing, green purchasing, cooperation with customers, eco-design, and green information system. Furthermore, adding institutional pressures as a moderator between GSCM and sustainable performance adds to the novelty and uniqueness of the research. The managerial implications have also been discussed.